Pengaruh Atraktan Limbah Ikan Pada Fly Trap Sebagai Penurunan Kepadatan Lalat Di Pasar Tradisional Srikerthi Desa Padangsambian Kelod Tahun 2023 - Putra, I Gede Arianata; Yulianti, Anysiah Elly; Hadi, M. Choirul; Sali, I Wayan (Poltekkes Kemenkes Denpasar, 2024)
Flies insects that transmit several diseases to humans. A way to control fly density using fly traps with addition fish waste attractants. With aim to determine effect adding fish waste attractants the fly trap decrease fly density. This research method is Pre Experiment research with design model One Group Pre Test Post Test Control, with Paired T-Test data analysis. The results showed there was effect adding fish waste attractants fly trap. Based on results the Paired t-test, count of 3.586 was obtained and sig value (0.006) alpha = (0.05). From results study before installation highest fly trap pointI of 8 tails in high and lowest categories pointIX, X of 2 tails low category, after installation highest fly trap point II of 4 tails in medium category and lowest points VII,IX,X of 1 tail the low category. It can be concluded that there is an effect of adding fish waste attractants fly trap as a decrease fly density.